(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
The present study was carried out to determine the physicochemical parameters of industrial effluents and to find out suitable macrophytes in removing metals from wastewater in order to enhance surface water treatment systems. The effluent samples, effluent free water and aquatic macrophytes were collected from Savar region. Higher values of temperature (56°C), pH (12.32), electrical conductivity (12375 ?S/cm), biochemical oxygen demand (835 mg/L), total suspended solids (2187 mg/L), total dissolved solids (6952 mg/L), turbidity (89.53 NTU) and total organic carbon (421.6 mg/L) were recorded in industrial effluents comparing with control. The lowest concentration of DO in industrial effluents (0.12 mg/L) was much lower than the control (5.65 mg/L). The concentration of Cr (0.69 mg/L), Se (0.08 mg/L), Pb (0.23 mg/L) and Cu (0.71 mg/L) in the effluent exceeded the limit of DOE. Although the concentration of Cd (0.017 mg/L), Li (0.019 mg/L), Ni (0.7 mg/L) and Zn (0.38 mg/L) of effluent water were within the limit of DOE, but were much higher than the control water. The cultures of aquatic macrophytes, Eichornia crassipes, Pistia stratoites and Salvinia cucullata using textile-dyeing effluent can efficiently uptake metals from the effluent. The uptake of metals increased with raising effluent concentration in relation to control culture. When cultured in 100% effluent, Eichornia crassipes, Pistia stratoites and Salvinia cucullata can uptake relatively high amount of Cr, Cd, Cu, Li, Ni, Zn, Co, Se and Pb compared to other two cultures (control, 50% effluent). At 100% effluent water, Eichornia crassipes and Pistia stratoites can uptake more than 90% Co and 80% Se and Pb with low survival capacity. Salvinia cucullata can efficiently absorb Cr, Cd, Li, Ni and Pb with long time survival capacity. While individually Pistia stratoites is more effective in absorbing Cu, Zn and Eichornia crassipes for absorbing Co and Pb in order to enhance surface water treatment system. Bangladesh J. Sci. Ind. Res. 48(2), 89-96, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15738